2009
DOI: 10.1007/s00221-009-1759-8
|View full text |Cite
|
Sign up to set email alerts
|

Sound enhances touch perception

Abstract: Certain sounds, such as fingernails screeching down a chalkboard, have a strong association with somatosensory percepts. In order to assess the influences of audition on somatosensory perception, three experiments measured how task-irrelevant auditory stimuli alter detection rates for near-threshold somatosensory stimuli. In Experiment 1, we showed that a simultaneous auditory stimulus increases sensitivity, but not response biases, to the detection of an electrical cutaneous stimulus delivered to the hand. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 44 publications
5
64
0
1
Order By: Relevance
“…There have been previous demonstrations of auditory-somatosensory interactions in situations other than speech (Jousmaki and Hari 1998;Ro et al 2009;Yau et al 2009;Zampini and Spence 2004). In particular, there are robust effects of auditory input on tactile frequency discrimination, and the auditory cross-sensory interference is quite specific.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There have been previous demonstrations of auditory-somatosensory interactions in situations other than speech (Jousmaki and Hari 1998;Ro et al 2009;Yau et al 2009;Zampini and Spence 2004). In particular, there are robust effects of auditory input on tactile frequency discrimination, and the auditory cross-sensory interference is quite specific.…”
Section: Discussionmentioning
confidence: 92%
“…The effects of auditory inputs on somatosensory perception have been reported in cases other than speech. For example, the detection of nearthreshold somatosensory stimuli is improved by the presence of simultaneous auditory inputs (Ro et al 2009). Similarly, the perception of surface roughness is affected by sounds played to subjects while they rub their hands together (Jousmaki and Hari 1998).…”
mentioning
confidence: 99%
“…Thus, higher frequency tactile vibrations on the hand are congruent both with higher levels of visual brightness (white shapes rather than black shapes) (Martino & Marks, 2000) and with higher levels of auditory pitch (Ro, Hsu, Yasar, Elmore & Beauchamp, 2009). Tactile sensations on the hand that are located higher in space also prove to be congruent with higher pitch sounds (Occelli, Spence, & Zampini, 2009).…”
Section: Judging the Mapping Of Cross-sensory Features Beyond Auditormentioning
confidence: 99%
“…Consistent with this phenomenology, several recent behavioral studies have demonstrated systematic perceptual interactions between the auditory and somatosensory modalities. For example, auditory sounds at one frequency affect the perception of somatosensory vibrations at the same or similar frequencies (Ro et al 2009;Yau et al 2009;Wilson et al 2010), somatosensory vibrations influence the perceived intensity of auditory stimuli (Yau et al 2010), somatosensory stimuli can influence the perception of language (Gick and Derrick 2009;Ito et al 2009) and vice versa (Ito and Ostry 2012), and higher auditory frequencies and intensities can alter texture perception (Jousmaki and Hari 1998;Guest et al 2002). Such results suggest the existence of highly tuned multisensory integration mechanisms for gathering consistent information about the environment, such as when hearing and feeling one's hand rubbing over textured surfaces.…”
Section: Introductionmentioning
confidence: 99%